(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This study explores the key mechanisms required for effectively managing investments and successfully implementing projects within the railway transport sector. It emphasizes the importance of addressing infrastructure aging, attracting private investors, and fostering public-private partnerships. By analyzing investment processes, risks, and the strategic management of resources, the research identifies steps to enhance the investment environment, improve infrastructure, and boost the sector’s competitiveness.